Abortion From A Right-To-Choice Perspective: Contributions From Comparative Jurisprudence And Public Policy - Casusol, Marco Ramírez (Journal of Neonatal Surgery, 2025)
The purpose of the study was to expose the way in which comparative jurisprudence and public policies have accepted abortion on the basis of the right to decide. From a qualitative approach, of a basic type and with a grounded theory design, and applying the documentary source analysis technique in a systematic, hermeneutic and critical way, it is hypothesized that the right to decide has become a human right that allows people to assume, in certain circumstances, important decisions with social, legal, ethical and political repercussions, as in this case, the decision to have an abortion. Thus, the discussion on this issue goes beyond the entrapment of restrictive positions of rights. Along these lines, in several countries the discussion and possibility of regulating this figure has been opened in the understanding that human freedom, a fundamental aspect of the right to decide, continues to be an aspiration that sustains any norm or position that goes against it.